BIODEGRADATION OF PULP SLUDGE BY Phanerochaete chrysosporium, Penicillium oxalicum and Penicillium citrinum AFTER SIX MONTHS INCUBATION - Wahyuningsih, Siti (Association of Indonesian Forestry and Environment Researchers and Technicians, 2019)
The rise of pulp and paper production due to market’s demand will also increase both main and secondary products of pulp. Secondary products such as pulp sludge have low economic value, but high environmental cost. Therefore it needs improved technology input to raise its value. This study aims to evaluate the ability of Phanerochaete chrysosporium, a combination of Penicillium citrinum and P. oxalicum and a mixture of those three fungal species in decomposing pulp sludge after one and six months incubation. The pulp sludge was collected from pulp company in North Sumatera, Indonesia and it was pre-treated prior to composting. The composting was conducted by inoculating P. chrysosporium, a combination of P. oxalicum and P. citrinum or a mixture of those fungal species with a density of 107 spores/ml into 15 kg treated sludge. The inoculated sludge was then incubated for one and six months. Analysis was held for the non-inoculated and inoculated sludge regarding pH, cation exchange capacity (CEC) (me/100 g), macronutrients (N, P, K, Ca and Mg) (%), micronutrients (S, Zn) (ppm) and heavy metals (Pb, Cd) (ppm). After one month incubation, P. chrysosporium was leading in enhancing sludge’s macro and micronutrients. After six months incubation, a combination of P. oxalicum and P. citrinum generated higher P, K, CEC and reduced lead content of the sludge. Meanwhile, a mixture of the three fungus species produced the highest N and Mg.